Methodological aspects of measuring the corruption situation in Hungary in a scientifically substantiated manner (Academic Journal of Internal Affairs, 2021)
Measuring corruption in a manner that is not substantiated scientifically and consequently elaborating international ranking lists may result in serious consequences, public condemnation of certain countries, as well as economic disadvantages. A fundamental prerequisite to effectively prevent and fight corruption is to have adequate information available about its scope and nature. Therefore, it is of utmost importance for the measurement system to be scientifically reliable and valid. In order to be able to assess the corruption situation in Hungary in a balanced and true manner, the study outlines the most important professional requirements and scientific standards in relation to the corruption measurement system, using the State Audit Office of Hungary’s studies on the reliability of corruption measurement, the results of its Integrity Survey, and the literature on corruption measurement and research methodology. It points out that corruption as a whole cannot be measured, however it is feasible to examine certain elements thereof. Thus, separately and with the adequate tools, for example the following can be examined: people’s attitude towards corruption, perception of corruption, their experience, as well as corruption risks and anti-corruption measures. Professional and organizational independence of the organization carrying out the assessment is a must, when it comes to unbiased measurement offering an objective view on the corruption phenomenon examined. The subject of the research must be made clear, the basic precondition for the measurement being the clear and exact definition of corruption and the related terms that also complies with the unique features of national legislation and values. An exact definition of the objective and the questions of the research is also essential, as these will determine the methods and the scope of the assessment, the parties concerned, the presentation of the results and the utilization thereof. The methodology and data sources of the research shall be presented in a way and to such extent that users can make sure, based thereon, that the research is substantiated and independent, researchers or research teams are able to repeat the research. Results of the research shall be presented professionally, in an objective manner, so that the planning of anti-corruption measures and interventions is made possible based on them. When formulating conclusions, special attention must be paid not to blur the lines between corruption-related phenomena and terms.
Keywords: corruption research; corruption phenomena; corruption perceptions; measuring corruption